Book Review: The Mushroom at the End of the World (2015) by Anna Lowenhaupt Tsing - Agung Wicaksono (Universitas Muhammadiyah Sumatera Utara, 2022)
This article is a book review by Dr. Anna Lowenhaupt Tsing's The Mushroom at the End of the World. This book is a work of cultural anthropology published in 2015 by Princeton University Press. Tsing is a cultural anthropologist specializing in Southeast Asia. Her work is thematically related to culture, marginalization, environmental activism, gender, and political economy. Currently, Tsing is a professor of anthropology at the University of California, Santa Cruz. The Mushroom at the End of the World is a field research-based book that covers various historical eras, geographic boundaries, and cultural contexts. Tsing aspires to explain how humanity came into being and how other living things built their worlds. Tsing points out that there is no aspect of life that is not worth investigating, including when she talks about the mushroom plant and its correlation with many things in human life